EFFECT OF FS, SG, AS AND NDTS TO CAPITAL STRUCTURE ON COMPANY PROPERTY AND REAL ESTATE - Angel Novelly; Sauh Hwee Teng; Sherlyn Wijaya; Christina Christina; Cyntia Arianti (Lembaga Layanan Pendidikan Tinggi Wilayah X, 2022)
Background : Between 2016 and 2020, the population used was 46 listed property and real estate company on the IDX. The sample selection technique is technique purposive sampling and obtained as much 14 sample company multiplied with five year, produce 70 units analysis. Research tested with use linear regression analysis multiple. Method : The data collection method in this research is document. Result : This research proves that Firm Size partially has no effect on the Capital Structure of property and real estate companies. This is due to personnel errors in the company in making decisions so that it becomes a wrong step that can be fatal in managing company funds or capital Conclusion : Firm Size, Sales Growth, Asset Structure, and Non Debt Tax Shield simultaneously have a significant positive effect on the Capital Structure of property and real estate companies listed on the IDX in 2016-2020.